2021
DOI: 10.3390/su13042412
|View full text |Cite
|
Sign up to set email alerts
|

Innovative or Not? The Effects of Consumer Perceived Value on Purchase Intentions for the Palace Museum’s Cultural and Creative Products

Abstract: A museum’s core activities traditionally focus on such areas as collections’ care, exhibitions and scholarship. Income generation, including retail activities, is considered secondary[...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 60 publications
0
19
0
Order By: Relevance
“…The analysis of any kind of conflict that may exist between the cultural missions of organisations and the broader goals of sustainable development also seems to be an important and, as yet, not fully explored issue. It is also worth extending the study of cultural institutions from the point of view of marketing management [58], or the offer for people buying souvenirs, increasingly produced organically, at cultural institutions-if, of course, the units in question have gadget shops on offer [59].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of any kind of conflict that may exist between the cultural missions of organisations and the broader goals of sustainable development also seems to be an important and, as yet, not fully explored issue. It is also worth extending the study of cultural institutions from the point of view of marketing management [58], or the offer for people buying souvenirs, increasingly produced organically, at cultural institutions-if, of course, the units in question have gadget shops on offer [59].…”
Section: Discussionmentioning
confidence: 99%
“…The final survey was conducted both in-person and online, with the sample population consisting of visitors that were visiting the park as well as visitors that had recently been to the park. Combining onsite and online surveys has been used in previous studies and was approved to be effective ( Li, Shu, Shao, Booth, & Morrison, 2021 ; Milohnić, Cvelić-Bonifačić, & Licul, 2019 ; Modrow, Tuck, Qian, Yu, & Haataja, 2021 ; Yuen, Tang, Lee, & Cheng, 2021 ). Providing two ways of surveying helps recruit large and more diverse samples ( Birnbaum, 2004 ), and having an online survey option can also minimize contact and reduce the risk of spreading disease during the COVID-19 pandemic.…”
Section: Methodsmentioning
confidence: 99%
“…It allows understanding the likelihood of purchase and the perceived value of museum attributes for tourists and residents interviewed, taking into account the choice experiments and willingness to pay. Previous research identified that applying methods such as the likelihood of purchase, willingness to pay and a choice experiment can contribute to developing sustainable management strategies [65,67]. Knowledge of museum attributes as perceived by both tourists and the local community provides us with data of interest for implementing sustainability strategies in museums and improving quality and experience (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…strategies [65,67]. Knowledge of museum attributes as perceived by both tourists and the local community provides us with data of interest for implementing sustainability strategies in museums and improving quality and experience (Figure 5).…”
Section: Discussionmentioning
confidence: 99%